Drilling fluid plugging agent based on modified resin and fiber
By using a combination sealant of modified resin and fiber in the drilling fluid, the problem of insufficient strength of the existing drilling fluid sealant under high pressure and high temperature conditions is solved, and higher temperature resistance and pressure bearing strength are achieved, reducing costs and improving safety and environmental friendliness.
Patent Information
- Application Number
- CN202510022250.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
The existing drilling fluid sealant is insufficient in complex formation conditions such as high pressure, high temperature, and high permeability, which can easily cause well leakage, blowout and other accidents, and is costly and difficult to widely use.
The drilling fluid sealing agent based on modified resin and fiber is used to improve the temperature resistance and pressure bearing strength of the sealing agent by modifying the combination of phenolic resin, epoxy resin, urea formaldehyde resin, polyester fiber and glass fiber.
It significantly improves the temperature resistance and pressure bearing strength of the sealant, reduces drilling fluid leakage, improves the stability of the well wall and reservoir protection effect, and reduces the toxicity of the drilling fluid, avoiding potential threats to the environment and human health.
Smart Images

Figure BDA0005231719930000091 
Figure BDA0005231719930000092 
Figure BDA0005231719930000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, in particular to a drilling fluid plugging agent based on modified resin and fiber. Background Art
[0002] Drilling fluid is a circulating fluid used in the drilling process. Its main functions are to cool the drill bit, carry cuttings, suspend cuttings, and control the stability of the wellbore. In the field of oil drilling technology, especially in the drilling and production of deep wells, ultra-deep wells and high-temperature formations, the formation conditions are complex and changeable, and the performance requirements of drilling fluids are extremely high. Under complex formation conditions, traditional drilling fluids may not meet the requirements, so more treatment agents need to be added to the drilling fluid to enhance its performance in high temperature, high pressure, corrosive environments, etc.
[0003] In the field of chemical engineering, modification refers to changing the properties or structure of a material by physical or chemical methods to meet specific application requirements. In the field of materials science, modification refers to improving the performance of a material or giving it new properties by adding other substances or changing its structure.
[0004] The current drilling fluid plugging technology shows a diversified development trend.
[0005] Physical plugging relies on optimizing the particle size, shape and distribution of solid particles in the drilling fluid to construct a dense filter cake to block the drilling fluid from entering the formation, such as using calcium carbonate, quartz sand and other particles for reasonable grading.
[0006] Chemical plugging achieves plugging by reacting chemical agents or interacting with formation rocks to form gels, precipitates or polymer films. For example, phenolic resins and epoxy resins cross-link to form a hard plugging layer, and polymers adsorb and cross-link to form films.
[0007] Nano plugging can penetrate deep into micro-cracks and pores in the formation due to the small particle size and large specific surface area of nanomaterials. For example, nanographene and silica can enhance the plugging of tiny pores. Composite plugging integrates the advantages of physical and chemical plugging, compounding rigid particles with polymer emulsions to enhance the strength and stability of the plugging layer. This technology has significant advantages. First, the stability of the well wall is enhanced, effectively blocking the penetration of drilling fluid filtrate into the formation, reducing the risk of hydration expansion and strength attenuation of formation rocks, effectively preventing well wall collapse and shrinkage, and ensuring smooth drilling operations. Second, the reservoir protection effect is good, plugging formation pores and cracks, reducing drilling fluid pollution and damage to the reservoir, maintaining reservoir permeability and porosity, and helping to improve the recovery rate of oil and gas fields.
[0008] However, the problem with the existing technology is that the plugging strength of the existing plugging agents is often insufficient. In the face of complex formations such as high pressure, high temperature, and high permeability, the strength of the plugging layer formed by the existing plugging technology is difficult to meet the requirements, which can easily cause accidents such as leaks and blowouts. This problem is particularly prominent when developing deep oil and gas reservoirs. Secondly, the plugging agent has poor affinity with the formation. Some plugging agents have large differences in surface properties with the formation rock. They have weak adhesion to the well wall and formation pores, are easy to fall off or be washed away, and are difficult to adapt to the differences in rock composition and pore structure in different formations. Furthermore, the cost is high. High-performance plugging agents such as nano plugging agents and special resin plugging agents have high preparation costs and large usage, which greatly increases the cost of drilling fluids and limits their widespread application. Summary of the invention
[0009] To solve at least one of the above problems, the present invention provides a drilling fluid plugging agent based on modified resin and fiber.
[0010] The technical scheme of the present invention is: a drilling fluid plugging agent based on modified resin and fiber, which comprises, by weight, 30 to 40 parts of modified phenolic resin, 5 to 15 parts of modified epoxy resin, 40 to 50 parts of modified urea-formaldehyde resin, 10 to 20 parts of modified polyester fiber, and 15 to 25 parts of modified glass fiber; the modified phenolic resin is prepared by modifying phenolic resin with ethyl silicate, the modified epoxy resin is prepared by reacting carbon nanotubes grafted with a silane coupling agent and epoxy resin, the modified urea-formaldehyde resin is prepared by reacting diisocyanate and urea-formaldehyde resin, the modified polyester fiber is prepared by reacting a silane coupling agent and polyester fiber, and the modified glass fiber is prepared by reacting boric acid ester and glass fiber etched with hydrofluoric acid.
[0011] One embodiment of the present invention is that the preparation method of the modified phenolic resin comprises the following steps: dissolving phenolic resin and ethyl silicate in a mass ratio of 1:0.2-0.4 in toluene, adding a catalyst, and reflux reacting at 50-60°C for 4-5h. After the reaction is completed, curing at 140-160°C in a mold for 2-3h, and crushing to obtain; the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.5-1% of the mass of the urea-formaldehyde resin.
[0012] One embodiment of the present invention is that the preparation method of the modified epoxy resin comprises the following steps: taking carbon nanotubes, adding them to a first solvent and dispersing them, then dropping a silicon coupling agent, reacting them for 4 to 6 hours under deoxygenation and 40 to 50° C., and after the reaction is completed, separating, purifying and drying them to obtain modified carbon nanotubes, wherein the amount of the silicon coupling agent added is 20 to 35% of the mass of the carbon nanotubes; taking epoxy resin, adding a dispersant and modified carbon nanotubes and stirring them evenly, heating them to 60° C., continuously shearing them at 5000 r / min for 1 to 2 hours, adding an epoxy resin curing agent and mixing them evenly, pouring them into a mold, heating them to 160° C. and curing them for 3 to 4 hours, and crushing and screening them after curing to obtain them; the amount of the modified carbon nanotubes added is 1 to 5% of the mass of the epoxy resin, and the amount of the dispersant BYK added is 2 to 5% of the mass of the epoxy resin.
[0013] Furthermore, the first solvent is toluene or xylene, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane, the epoxy resin is at least one of E-44 or E-55, the epoxy resin curing agent is pentaethylenetetramine, and the mass ratio of the epoxy resin to the epoxy resin curing agent is 100:15 to 18.
[0014] One embodiment of the present invention is that the preparation method of the modified urea-formaldehyde resin comprises the following steps: taking a urea-formaldehyde resin and a diisocyanate in a mass ratio of 5 to 10:1 and dissolving them in a second solvent, adding a catalyst, and reflux reacting at 50 to 70°C for 3 to 5 hours. After the reaction is completed, pouring into a mold, curing at 140°C for 3 hours, and crushing and screening to obtain; the second solvent is toluene, the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.5 to 1% of the mass of the urea-formaldehyde resin.
[0015] One embodiment of the present invention is that the preparation method of the modified polyester fiber comprises the following steps: taking a silane coupling agent and dissolving it, then adding the polyester fiber, reacting at 40 to 60° C. for 4 to 6 hours, and after the reaction is completed, separating, purifying, drying and sieving the modified polyester fiber; the amount of the silane coupling agent added is 1 to 5% of the mass of the polyester fiber, and the silane coupling agent is at least one of γ-aminopropyltriethoxysilane and N-aminoethyl-3-aminopropylmethyldimethoxysilane.
[0016] One embodiment of the present invention is that the preparation method of the modified glass fiber comprises the following steps: taking glass fiber, etching it with hydrofluoric acid, washing, drying and crushing it after etching to obtain the etched glass fiber; taking the etched glass fiber and boric acid ester with a mass ratio of 5 to 8:1, adding solvent and triethylamine, reacting at 60 to 80°C for 3 to 5 hours, and separating and purifying it after the reaction is completed; the amount of triethylamine added is 0.5 to 1% of the mass of the modified glass fiber.
[0017] Beneficial effects: 1. The present invention adopts a specific modification method to make the plugging agent have excellent temperature resistance and pressure bearing strength. 2. The modification method adopted by the present invention will not change the viscosity and other rheological properties of the drilling fluid, so as not to affect the pumpability and fluidity of the drilling fluid, which has obvious advantages over the prior art. 3. The modification method of the present invention can improve the performance of the drilling fluid without increasing the toxicity of the drilling fluid, so as not to cause potential threats to the environment and human health, which has significant advantages over the prior art. 4. The modification method of the present invention can improve the thermal stability and temperature and salt resistance of the drilling fluid, so that it can more effectively fill and adsorb on the formation surface when plugging the formation pores under high temperature and high pressure conditions in the formation, reduce drilling fluid loss, and further improve the performance of the drilling fluid. DETAILED DESCRIPTION
[0018] The specific implementation modes of the present invention will be described clearly and completely below with reference to examples. Obviously, the examples described are only some embodiments of the present invention, rather than all embodiments.
[0019] In the following embodiments, the screening operation refers to placing a 100-mesh standard sieve on a 120-mesh standard sieve, placing the crushed particles into the 100-mesh standard sieve, and shaking back and forth until no particles pass through the upper and lower standard sieves, and retaining the particles in the 120-mesh standard sieve.
[0020] Example 1
[0021] The plugging agent of this embodiment includes 30 parts of modified phenolic resin, 6 parts of modified epoxy resin, 45 parts of modified urea-formaldehyde resin, 12 parts of modified polyester fiber, and 15 parts of modified glass fiber.
[0022] The preparation method of the modified phenolic resin is as follows: dissolve phenolic resin and ethyl silicate in toluene at a mass ratio of 1:0.2, wherein the total concentration of phenolic resin and ethyl silicate is 25 g / L, add a catalyst, and reflux for 4 hours at 50°C. After the reaction is completed, cure in a mold at 140°C for 2 hours, crush and sieve to obtain the modified phenolic resin; the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.5% of the mass of the urea-formaldehyde resin.
[0023] The preparation method of the modified epoxy resin is as follows: take carbon nanotubes, add them into toluene and disperse them, then drop a silane coupling agent, reflux for 4 hours under deoxygenation and 40°C conditions, separate, purify and dry them after the reaction to obtain the modified carbon nanotubes, wherein the amount of the silane coupling agent added is 20% of the mass of the carbon nanotubes; take epoxy resin E-44, add dispersant BYK (BYK, Germany) and modified carbon nanotubes and disperse them uniformly, heat to 60°C and shear at 5000r / min for 1h, then add pentaethylenetetramine and mix them uniformly, pour them into a mold, heat to 160°C and cure for 3h, take the cured epoxy resin, crush it and sieve it to obtain the modified carbon nanotubes, wherein the amount of the modified carbon nanotubes added is 1.5% of the mass of the epoxy resin, the amount of the dispersant BYK added is 2% of the mass of the epoxy resin, and the amount of the pentaethylenetetramine added is 17% of the mass of the epoxy resin.
[0024] The preparation method of the modified urea-formaldehyde resin is as follows: take urea-formaldehyde resin and diisocyanate in a mass ratio of 5:1 and dissolve them in a second solvent, add a catalyst, reflux at 70°C for 3.5 hours, pour into a mold after the reaction is completed, cure at 140°C for 3 hours, and crush and screen to obtain; the second solvent is toluene, the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.5% of the mass of the urea-formaldehyde resin.
[0025] The preparation method of the modified polyester fiber is as follows: taking a silane coupling agent and dissolving it, then adding the polyester fiber, and reflux reacting at 60° C. for 4 hours. After the reaction is completed, separating, purifying, drying and sieving the modified polyester fiber; the amount of the silane coupling agent added is 1% of the mass of the polyester fiber, and the silane coupling agent is γ-aminopropyltriethoxysilane.
[0026] The preparation method of the modified glass fiber is as follows: take glass fiber, etch it with hydrofluoric acid, wash, dry and crush it after etching to obtain the etched glass fiber; take the etched glass fiber and borate with a mass ratio of 5:1, add solvent and triethylamine, reflux reaction at 60°C for 3h, and after the reaction is completed, separate, purify and screen it to obtain the modified glass fiber; the amount of triethylamine added is 0.5% of the mass of the modified glass fiber.
[0027] Embodiment 2:
[0028] The plugging agent of this embodiment includes 38 parts of modified phenolic resin, 8 parts of modified epoxy resin, 45 parts of modified urea-formaldehyde resin, 15 parts of modified polyester fiber, and 20 parts of modified glass fiber.
[0029] The preparation method of the modified phenolic resin is as follows: dissolve phenolic resin and ethyl silicate in toluene at a mass ratio of 1:0.3, wherein the total concentration of phenolic resin and ethyl silicate is 25 g / L, add a catalyst, and reflux for 4.5 hours at 55° C. After the reaction is completed, cure in a mold at 150° C. for 2 hours, crush and sieve to obtain; the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.8% of the mass of the urea-formaldehyde resin.
[0030] The preparation method of the modified epoxy resin is as follows: take carbon nanotubes, add them into toluene and disperse them, then drop a silane coupling agent, reflux for 5 hours under deoxygenation and 50°C conditions, separate, purify and dry them after the reaction to obtain the modified carbon nanotubes, wherein the amount of the silane coupling agent added is 22% of the mass of the carbon nanotubes; take epoxy resin E-51, add dispersant BYK (BYK, Germany) and modified carbon nanotubes and disperse them uniformly, heat to 60°C and shear at 5000r / min for 1.5h, then add pentaethylenetetramine and mix them uniformly, pour them into a mold, heat to 160°C and cure for 3.5h, take the cured epoxy resin, crush and sieve it to obtain the modified carbon nanotubes, wherein the amount of the modified carbon nanotubes added is 2.5% of the mass of the epoxy resin, the amount of the dispersant BYK added is 3% of the mass of the epoxy resin, and the amount of the pentaethylenetetramine added is 16% of the mass of the epoxy resin.
[0031] The preparation method of the modified urea-formaldehyde resin is as follows: take a urea-formaldehyde resin and a diisocyanate in a mass ratio of 10:1 and dissolve them in a second solvent, add a catalyst, reflux at 55°C for 4 hours, pour into a mold after the reaction is completed, cure at 140°C for 3 hours, and crush and screen to obtain the modified urea-formaldehyde resin; the second solvent is toluene, the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.6% of the mass of the urea-formaldehyde resin
[0032] The preparation method of the modified polyester fiber is as follows: taking a silane coupling agent and dissolving it, then adding the polyester fiber, reacting it at 55°C reflux condition for 4 hours, and after the reaction is completed, separating, purifying, drying and sieving it to obtain the modified polyester fiber; the amount of the silane coupling agent added is 4% of the mass of the polyester fiber, and the silane coupling agent is N-aminoethyl-3-aminopropylmethyldimethoxysilane.
[0033] The preparation method of the modified glass fiber is as follows: taking glass fiber, etching it with hydrofluoric acid, washing, drying and crushing it after etching to obtain the etched glass fiber; taking the etched glass fiber and boric acid ester with a mass ratio of 6:1, adding solvent and triethylamine, reflux reaction at 60°C for 5h, and after the reaction is completed, separating, purifying and screening it to obtain the modified glass fiber; the amount of triethylamine added is 1% of the mass of the modified glass fiber.
[0034] Example 3
[0035] The plugging agent of this embodiment includes 39 parts of modified phenolic resin, 12 parts of modified epoxy resin, 48 parts of modified urea-formaldehyde resin, 18 parts of modified polyester fiber, and 20 parts of modified glass fiber.
[0036] The preparation method of the modified phenolic resin is as follows: dissolve phenolic resin and ethyl silicate in toluene at a mass ratio of 1:0.35, wherein the total concentration of phenolic resin and ethyl silicate is 25 g / L, add a catalyst, and reflux for 4.5 hours at 60°C. After the reaction is completed, cure in a mold at 155°C for 2 hours, crush and sieve to obtain the modified phenolic resin; the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 1% of the mass of the urea-formaldehyde resin.
[0037] The preparation method of the modified epoxy resin is as follows: take carbon nanotubes, add them into toluene and disperse them, then drop a silane coupling agent, reflux for 6 hours under deoxygenation and 55°C conditions, separate, purify and dry them after the reaction to obtain the modified carbon nanotubes, wherein the amount of the silane coupling agent added is 32% of the mass of the carbon nanotubes; take epoxy resin E-44, add dispersant BYK (BYK, Germany) and modified carbon nanotubes and disperse them uniformly, heat to 60°C and shear at 5000r / min for 1h, then add pentaethylenetetramine and mix them uniformly, pour them into a mold, heat to 160°C and cure for 3.5h, take the cured epoxy resin, crush and sieve it to obtain the modified carbon nanotubes, wherein the amount of the modified carbon nanotubes added is 2.5% of the mass of the epoxy resin, the amount of the dispersant BYK added is 2% of the mass of the epoxy resin, and the amount of the pentaethylenetetramine added is 17% of the mass of the epoxy resin.
[0038] The preparation method of the modified urea-formaldehyde resin is as follows: take a urea-formaldehyde resin and a diisocyanate in a mass ratio of 7:1 and dissolve them in a second solvent, add a catalyst, reflux at 70°C for 4.5 hours, pour into a mold after the reaction is completed, cure at 140°C for 3 hours, and crush and screen to obtain; the second solvent is toluene, the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.7% of the mass of the urea-formaldehyde resin
[0039] The preparation method of the modified polyester fiber is as follows: taking a silane coupling agent and dissolving it, then adding the polyester fiber, and reflux reacting at 75° C. for 3.5 hours. After the reaction is completed, separating, purifying, drying and sieving the modified polyester fiber; the amount of the silane coupling agent added is 1.5% of the mass of the polyester fiber, and the silane coupling agent is γ-aminopropyltriethoxysilane.
[0040] The preparation method of the modified glass fiber is as follows: take glass fiber, etch it with hydrofluoric acid, wash, dry and crush it after etching to obtain the etched glass fiber; take the etched glass fiber and borate with a mass ratio of 6.5:1, add solvent and triethylamine, reflux reaction at 50°C for 4.5h, and after the reaction is completed, separate, purify and screen it to obtain the modified glass fiber; the amount of triethylamine added is 1% of the mass of the modified glass fiber.
[0041] Example 4
[0042] The plugging agent of this embodiment includes 40 parts of modified phenolic resin, 15 parts of modified epoxy resin, 50 parts of modified urea-formaldehyde resin, 15 parts of modified polyester fiber, and 18 parts of modified glass fiber.
[0043] The preparation method of the modified phenolic resin is as follows: dissolve phenolic resin and ethyl silicate in toluene at a mass ratio of 1:0.35, wherein the total concentration of phenolic resin and ethyl silicate is 25 g / L, add a catalyst, and reflux for 5 hours at 60°C. After the reaction is completed, cure in a mold at 160°C for 2 hours, crush and sieve to obtain the modified phenolic resin; the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.9% of the mass of the urea-formaldehyde resin.
[0044] The preparation method of the modified epoxy resin is as follows: take carbon nanotubes, add them into toluene and disperse them, then drop a silane coupling agent, reflux for reaction for 5.5 hours under deoxygenation and 60°C conditions, separate and purify them after the reaction to obtain modified carbon nanotubes, wherein the amount of the silane coupling agent added is 25% of the mass of the carbon nanotubes; take epoxy resin E-44, add dispersant BYK (BYK, Germany) and modified carbon nanotubes and disperse them uniformly, heat to 60°C and shear at 5000r / min for 2h, then add pentaethylenetetramine and mix them uniformly, pour them into a mold, heat to 160°C and cure for 4h, take the cured epoxy resin, crush and sieve it to obtain, wherein the amount of the modified carbon nanotubes added is 2% of the mass of the epoxy resin, the amount of the dispersant BYK added is 2% of the mass of the epoxy resin, and the amount of the pentaethylenetetramine added is 17% of the mass of the epoxy resin.
[0045] The preparation method of the modified urea-formaldehyde resin is as follows: take a urea-formaldehyde resin and a diisocyanate in a mass ratio of 10:1 and dissolve them in a second solvent, add a catalyst, reflux at 55°C for 4 hours, pour into a mold after the reaction is completed, cure at 140°C for 3 hours, and crush and screen to obtain the modified urea-formaldehyde resin; the second solvent is toluene, the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.55% of the mass of the urea-formaldehyde resin
[0046] The preparation method of the modified polyester fiber is as follows: taking a silane coupling agent and dissolving it, then adding the polyester fiber, and reflux reacting at 55°C for 4 hours. After the reaction is completed, separating, purifying, drying and sieving the modified polyester fiber; the amount of the silane coupling agent added is 2.5% of the mass of the polyester fiber, and the silane coupling agent is γ-aminopropyltriethoxysilane and N-aminoethyl-3-aminopropylmethyldimethoxysilane, and the amount ratio of the substances is 1:1.
[0047] The preparation method of the modified glass fiber is as follows: take glass fiber, etch it with hydrofluoric acid, wash, dry and crush it after etching to obtain the etched glass fiber; take the etched glass fiber and borate with a mass ratio of 7.5:1, add solvent and triethylamine, reflux reaction at 60°C for 4h, and after the reaction is completed, separate, purify and screen it to obtain the modified glass fiber; the amount of triethylamine added is 0.85% of the mass of the modified glass fiber.
[0048] Example 5
[0049] The plugging agent of this embodiment includes 37 parts of modified phenolic resin, 13 parts of modified epoxy resin, 40 parts of modified urea-formaldehyde resin, 12 parts of modified polyester fiber, and 25 parts of modified glass fiber.
[0050] The preparation method of the modified phenolic resin is as follows: dissolve phenolic resin and ethyl silicate in toluene at a mass ratio of 1:0.38, wherein the total concentration of phenolic resin and ethyl silicate is 25 g / L, add a catalyst, and reflux for 5 hours at 55°C. After the reaction is completed, cure in a mold at 150°C for 3 hours, crush and sieve to obtain the modified phenolic resin; the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.95% of the mass of the urea-formaldehyde resin.
[0051] The preparation method of the modified epoxy resin is as follows: take carbon nanotubes, add them into toluene and disperse them, then drop a silane coupling agent, reflux for reaction for 5.5 hours under deoxygenation and 50°C conditions, separate, purify and dry them after the reaction to obtain the modified carbon nanotubes, wherein the amount of the silane coupling agent added is 33% of the mass of the carbon nanotubes; take epoxy resin E-44, add dispersant BYK (BYK, Germany) and modified carbon nanotubes and disperse them uniformly, heat to 60°C and shear at 5000r / min for 2h, then add pentaethylenetetramine and mix them uniformly, pour them into a mold, heat to 160°C and cure for 3h, take the cured epoxy resin, crush and sieve it to obtain the modified carbon nanotubes, wherein the amount of the modified carbon nanotubes added is 1.5% of the mass of the epoxy resin, the amount of the dispersant BYK added is 2% of the mass of the epoxy resin, and the amount of the pentaethylenetetramine added is 17% of the mass of the epoxy resin.
[0052] The preparation method of the modified urea-formaldehyde resin is as follows: take urea-formaldehyde resin and diisocyanate in a mass ratio of 8:1 and dissolve them in a second solvent, add a catalyst, reflux at 65°C for 4.5 hours, pour into a mold after the reaction, cure at 140°C for 3 hours, and crush and screen to obtain; the second solvent is toluene, the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.95% of the mass of the urea-formaldehyde resin.
[0053] The preparation method of the modified polyester fiber is as follows: taking a silane coupling agent and dissolving it, then adding the polyester fiber, and reflux reacting at 45° C. for 5 hours. After the reaction is completed, separating, purifying, drying and sieving the modified polyester fiber; the amount of the silane coupling agent added is 3.5% of the mass of the polyester fiber, and the silane coupling agent is γ-aminopropyltriethoxysilane.
[0054] The preparation method of the modified glass fiber is as follows: take glass fiber, etch it with hydrofluoric acid, wash, dry and crush it after etching to obtain the etched glass fiber; take the etched glass fiber and borate with a mass ratio of 7.5:1, add solvent and triethylamine, reflux reaction at 60°C for 4.5h, and after the reaction is completed, separate, purify and screen it to obtain the modified glass fiber; the amount of triethylamine added is 0.85% of the mass of the modified glass fiber.
[0055] Comparative Example 1
[0056] The plugging agent of this comparative example includes 30 parts of phenolic resin, 6 parts of modified epoxy resin, 45 parts of modified urea-formaldehyde resin, 12 parts of modified polyester fiber, and 15 parts of modified glass fiber.
[0057] Wherein, the preparation methods of the modified epoxy resin, the modified urea-formaldehyde resin, the modified polyester fiber and the modified glass fiber are the same as those in Example 1.
[0058] Comparative Example 2
[0059] The plugging agent of this comparative example includes 38 parts of modified phenolic resin, 8 parts of epoxy resin, 45 parts of modified urea-formaldehyde resin, 15 parts of modified polyester fiber, and 20 parts of modified glass fiber.
[0060] Among them, the preparation methods of the modified phenolic resin, modified urea-formaldehyde resin, modified polyester fiber and modified glass fiber are the same as those in Example 1.
[0061] Comparative Example 3
[0062] The plugging agent of this comparative example includes 39 parts of modified phenolic resin, 12 parts of modified epoxy resin, 48 parts of urea-formaldehyde resin, 18 parts of modified polyester fiber, and 20 parts of modified glass fiber.
[0063] Among them, the preparation methods of modified phenolic resin, modified epoxy resin, modified polyester fiber and modified glass fiber are the same as those in Example 1.
[0064] Comparative Example 4
[0065] The plugging agent of this comparative example includes 40 parts of modified phenolic resin, 15 parts of modified epoxy resin, 50 parts of modified urea-formaldehyde resin, 15 parts of polyester fiber, and 18 parts of modified glass fiber.
[0066] Among them, the preparation methods of modified phenolic resin, modified epoxy resin, modified urea-formaldehyde resin and modified glass fiber are the same as those in Example 1.
[0067] Comparative Example 5
[0068] The plugging agent of this comparative example includes 37 parts of modified phenolic resin, 13 parts of modified epoxy resin, 40 parts of modified urea-formaldehyde resin, 12 parts of modified polyester fiber, and 25 parts of glass fiber.
[0069] Among them, the preparation methods of modified phenolic resin, modified epoxy resin, modified urea-formaldehyde resin and modified polyester fiber are the same as those in Example 1.
[0070] In order to further illustrate the specific performance of the product obtained in the embodiment of the present invention, it is tested below.
[0071] 1. Viscosity
[0072] Take two high-speed stirring cups, add 400 mL of distilled water, 20.00 g (weighed to 0.01 g) bentonite for drilling fluid test slurry, and 0.60 g (weighed to 0.01 g) anhydrous sodium carbonate respectively, stir on a high-speed stirrer for 20 minutes, and then seal and cure at 25℃±1℃ for 24 hours.
[0073] 16.0 g of the plugging agents of Examples 1 to 5 and Comparative Examples 1 to 5 were added to the base slurry, respectively. The plugging agents and the base slurry were stirred at high speed for 10 min. The apparent viscosity of the base slurry and the sample slurry was measured according to the provisions of GB / T16783.1-2014.
[0074] The apparent viscosity increase was calculated according to the following formula. The results are shown in Table 1.
[0075] △AV=AV2-AV1
[0076] Where: △AV is the apparent viscosity increase value, mPa·s; AV1 is the apparent viscosity of the base slurry, mPa·s; AV2 is the apparent viscosity after adding the plugging agent, mPa·s.
[0077] Table 1 Apparent viscosity test results
[0078]
[0079] It can be seen from Table 1 that the plugging agent of the embodiment of the present invention has little effect on the viscosity of the drilling fluid and can be compatible with conventional drilling fluid.
[0080] 2. Pressure bearing capacity and filtration loss test
[0081] Prepare the base slurry in Test Example 1, and after closed curing at 25℃±1℃ for 24h, add 1mL of 40% sodium hydroxide solution while stirring at high speed, stir at high speed for 2min, then add 16g of plugging agent, stir at high speed for 10min, and then add 0.8g of xanthan gum (weighed to 0.01g), stir at high speed for 8min, interrupting twice to scrape off the adhesion on the container wall.
[0082] In the GGS71-B high-temperature and high-pressure filter loss instrument mud cup, without adding filter paper, directly add 500g of 60-80 mesh dry and clean quartz sand with a key to gently flatten the quartz sand in the slurry cup, and slowly add the sample slurry to the scale line by draining with a glass rod; install the mud cup cover, and conduct a pressure test. Before pressurizing, open the upper valve stem and slowly pressurize to 0.7MPa, stabilize the pressure for 30min, then slowly and evenly pressurize to 6.0MPa, stabilize the pressure for 15min, close the upper valve stem, release the pressure, and record the plugging filtration loss. The data is shown in Table 2.
[0083] Table 2 Pressure bearing capacity and filtration loss test results
[0084]
[0085]
[0086] It can be seen from Table 2 that the plugging agent of the embodiment of the present invention has a good plugging effect. Among them, the blank is an example of the plugging agent prepared by the embodiment of the present invention and the comparative example without adding.
[0087] Prepare the base slurry in Test Example 1, seal and cure at 25℃±1℃ for 24h, add 1mL of 40% sodium hydroxide solution while stirring at high speed, stir at high speed for 2min, add 16g of sample, stir at high speed for 10min, put into the aging kettle, heat roll at 200℃ for 24h, take out and cool to room temperature, then pour into a high stirring cup. Add 0.8g of xanthan gum, stir at high speed for 8min, interrupt twice to scrape off the adhesion on the container wall.
[0088] In the GGS71-B high-temperature and high-pressure filter loss instrument mud cup, without adding filter paper, directly add 500g of 60-80 mesh dry and clean quartz sand with a key to gently flatten the quartz sand in the slurry cup, and slowly add the sample slurry to the scale line by draining with a glass rod; install the mud cup cover, and conduct a pressure test. Before pressurizing, open the upper valve stem and slowly pressurize to 0.7MPa, stabilize the pressure for 30 minutes, then slowly and evenly pressurize to 6.0MPa, stabilize the pressure for 15 minutes, close the upper valve stem, release the pressure, and record the plugging filtration loss. The data is shown in Table 3.
[0089] Table 3 Test results of pressure bearing capacity and filtration loss after aging
[0090]
[0091]
[0092] It can be seen from Table 3 that the plugging agent of the embodiment of the present invention has good temperature resistance and can withstand a high temperature of 200°C.
[0093] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A drilling fluid plugging agent based on modified resin and fiber, characterized in that: The invention comprises, by weight, 30 to 40 parts of modified phenolic resin, 5 to 15 parts of modified epoxy resin, 40 to 50 parts of modified urea-formaldehyde resin, 10 to 20 parts of modified polyester fiber, and 15 to 25 parts of modified glass fiber; the modified phenolic resin is prepared by modifying phenolic resin with ethyl silicate, the modified epoxy resin is prepared by reacting carbon nanotubes grafted with silane coupling agent with epoxy resin, the modified urea-formaldehyde resin is prepared by reacting diisocyanate with urea-formaldehyde resin, the modified polyester fiber is prepared by reacting silane coupling agent with polyester fiber, and the modified glass fiber is prepared by reacting boric acid ester with glass fiber etched with hydrofluoric acid.
2. The plugging agent according to claim 1, characterized in that: The preparation method of the modified phenolic resin comprises the following steps: dissolving phenolic resin and ethyl silicate in a mass ratio of 1:0.2-0.4 in toluene, adding a catalyst, and performing a reflux reaction at 50-60°C for 4-5 hours. After the reaction is completed, solidifying, crushing and sieving the modified phenolic resin; the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.5-1% of the mass of the urea-formaldehyde resin.
3. The plugging agent according to claim 1, characterized in that: The preparation method of the modified epoxy resin comprises the following steps: taking carbon nanotubes, adding them into a first solvent and dispersing them, then dropping a silicon coupling agent, reacting them for 4 to 6 hours under deoxygenation and 40 to 50° C., and after the reaction is completed, separating, purifying and drying them to obtain modified carbon nanotubes, wherein the amount of the silicon coupling agent added is 20 to 35% of the mass of the carbon nanotubes; taking epoxy resin, adding a dispersant BYK and modified carbon nanotubes and stirring them evenly, heating to 60° C., stirring continuously for 1 to 2 hours, adding an epoxy resin curing agent and mixing them evenly, and crushing and sieving them after curing to obtain the modified carbon nanotubes; the amount of the modified carbon nanotubes added is 1 to 5% of the mass of the epoxy resin, and the amount of the dispersant BYK added is 5% of the mass of the epoxy resin.
4. The plugging agent according to claim 3, characterized in that: The first solvent is toluene or xylene, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane, the epoxy resin is at least one of E-44 or E-55, the epoxy resin curing agent is pentaethylenetetramine, and the mass ratio of the epoxy resin to the epoxy resin curing agent is 100:15 to 18.
5. The plugging agent according to claim 1, characterized in that: The preparation method of the modified urea-formaldehyde resin comprises the following steps: taking urea-formaldehyde resin and diisocyanate in a mass ratio of 5 to 10:1 and dissolving them in a second solvent, adding a catalyst, reacting at 50 to 70° C. for 3 to 5 hours, solidifying it after the reaction, and then separating, purifying and sieving it; the second solvent is toluene, the catalyst is dibutyltin dilaurate, and the amount of the catalyst added is 0.5 to 1% of the mass of the urea-formaldehyde resin.
6. The plugging agent according to claim 1, characterized in that: The preparation method of the modified polyester fiber comprises the following steps: taking and dissolving a silane coupling agent, then adding the polyester fiber, reacting at 40-60° C. for 4-6 hours, and after the reaction is completed, separating, purifying, drying and screening the modified polyester fiber; the amount of the silane coupling agent added is 1-5% of the mass of the polyester fiber, and the silane coupling agent is at least one of γ-aminopropyltriethoxysilane and N-aminoethyl-3-aminopropylmethyldimethoxysilane.
7. The plugging agent according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises the following steps: taking glass fiber, etching it with hydrofluoric acid, washing, drying and crushing it after etching to obtain the etched glass fiber; taking the etched glass fiber and boric acid ester with a mass ratio of 5 to 8:1, adding solvent and triethylamine, reacting at 60 to 80° C. for 3 to 5 hours, and separating and purifying it after the reaction is completed; the amount of triethylamine added is 0.5 to 1% of the mass of the modified glass fiber.
Citation Information
Cited By
Plugging agent suitable for malignant leakage formation as well as preparation method and application of plugging agent
CN120590929A
Phenolic resin microsphere-based porous carbon conductive composite material and preparation method thereof
CN122091301A